2022
DOI: 10.1136/bmj-2021-067516
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and adiposity indicators and risk of type 2 diabetes: systematic review and dose-response meta-analysis of cohort studies

Abstract: Objective To present a comprehensive review of the association between measures of body weight, waist, and fat, and different ratios of these measures, and the risk of type 2 diabetes. Design Systematic review and dose-response meta-analysis of cohort studies. Data sources PubMed, Scopus, and Web of Science up to 1 May 2021. Review methods Cohort studies looking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 55 publications
3
81
0
1
Order By: Relevance
“…A meta-analysis included ten observational studies involving 112,603 participants found that VAI may be related to a high risk of prediabetes [ 55 ]. A recent meta-analysis included nine cohort studies showed that each 1-unit increment of VAI was associated with 42% higher risk of T2DM [ 25 ]. Yu et al also conducted a cohort analysis and found that high-VAI level was associated with increased risk of new-onset T2DM [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis included ten observational studies involving 112,603 participants found that VAI may be related to a high risk of prediabetes [ 55 ]. A recent meta-analysis included nine cohort studies showed that each 1-unit increment of VAI was associated with 42% higher risk of T2DM [ 25 ]. Yu et al also conducted a cohort analysis and found that high-VAI level was associated with increased risk of new-onset T2DM [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, it is difficult to identify patients with MAFLD early and accurately based on BMI alone, so it is necessary to find better indicators of central obesity and insulin resistance (IR) to assist in the diagnosis of MAFLD. Easy-to-calculate and accessible anthropometric indicators such as lipid accumulation product (LAP), body roundness index (BRI), visceral fat index (VAI), cone index (CI), and body fat index (BAI) have been used as proxies for IR and central obesity and can quantify visceral fat status (20)(21)(22). In addition, the CMI, triglyceride-glucose (TyG) index, and hepatic steatosis index (HSI) have been confirmed to reflect adiposity and IR (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence and increasing incidence rates of overweight and obesity are major public health problems in Western societies due to their association with pathologies such as diabetes, cardiovascular diseases, and cancer [ 1 , 2 , 3 , 4 ]. On the other hand, overweight and obesity are also risk factors for a number of infectious diseases [ 5 ] and are associated with higher frequencies of nosocomial infections, including respiratory tract infections and pneumonia, as again recently discussed for COVID-19 patients [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%